1994
DOI: 10.1037/0022-3514.66.2.329
|View full text |Cite
|
Sign up to set email alerts
|

Person and contextual features of daily stress reactivity: Individual differences in relations of undesirable daily events with mood disturbance and chronic pain intensity.

Abstract: We examined the mood-related and pain-related consequences of daily stressors among 74 individuals with rheumatoid arthritis who supplied daily reports for 75 days. Meta-analyses of time series regression coefficients disclosed a significant same-day relation between events and mood but no consistent effects of events on same-day pain, next-day mood, or next-day pain. With distributional characteristics of the daily data controlled, Ss with more active inflammatory disease showed a greater positive relation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
147
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 171 publications
(163 citation statements)
references
References 66 publications
14
147
2
Order By: Relevance
“…Recent work by Affleck et a1 (17) has shown that stress associated with undesirable daily events is positively associated with arthritic pain. These associations were derived from end-of-day assessments taken over several weeks.…”
Section: Discussionmentioning
confidence: 98%
“…Recent work by Affleck et a1 (17) has shown that stress associated with undesirable daily events is positively associated with arthritic pain. These associations were derived from end-of-day assessments taken over several weeks.…”
Section: Discussionmentioning
confidence: 98%
“…Affleck, Tennen, Urrows & Higgins, 1994) among patient populations. We were interested in examining these associations among healthy adults to examine how seemingly transient experiences of health and affective well-being may have a greater effect on daily life than their definitions imply.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we did not examine how chronic strain and acute, daily stress work together to affect pain and mood across days. As Affleck et al (1990Affleck et al ( , 1994 have shown, it is a mistake to abstract one day out of the week, month or life of an individual with a disease like RA that changes from day-to-day. Future studies must examine how both paid and unpaid work events pile up over the week, the month, the year and with what effect on health.…”
Section: Discussionmentioning
confidence: 99%